2022
DOI: 10.1002/advs.202203902
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Endogenous H2S Activation of Self‐Assembled Nanoprobe with Controllable Biodegradation for Synergistically Enhanced Colon Cancer‐Specific Therapy

Abstract: Excessive production of hydrogen sulfide (H2S) plays a crucial role in the progress of colon cancer. Construction of tumor‐specific H2S‐activated smart nanoplatform with controllable biodegradation is of great significance for precise and sustainable treatment of colon cancer. Herein, an endogenous H2S triggered Co‐doped polyoxometalate (POM‐Co) cluster with self‐adjustable size, controlled biodegradation, and sustainable cyclic depletion of H2S/glutathione (GSH) is designed for synergistic enhanced tumor‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 46 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…Given that both Co 2+ and Cu + ions possess Fenton reactivity to generate hydroxyl radical (·OH) for CDT, we explored the CDT performance of the CoCuMo‐LDH nanosheets incubated in different pH environments containing GSH using 3,3’,5,5’‐tetramethylbenzidine (TMB) assay. [ 55,56 ] As indicated in Figure S11 (Supporting Information), a significant increase in TMB absorption is observed when the CoCuMo‐LDH nanosheets were incubated at pH 5.4 containing GSH. In contrast, the CoCuMo‐LDH nanosheets incubated at pH 7.4 and 6.5 with GSH show inconspicuous increase in TMB absorption, illustrating the pH‐responsive ·OH generation capacity of the CoCuMo‐LDH nanosheets.…”
Section: Resultsmentioning
confidence: 98%
“…Given that both Co 2+ and Cu + ions possess Fenton reactivity to generate hydroxyl radical (·OH) for CDT, we explored the CDT performance of the CoCuMo‐LDH nanosheets incubated in different pH environments containing GSH using 3,3’,5,5’‐tetramethylbenzidine (TMB) assay. [ 55,56 ] As indicated in Figure S11 (Supporting Information), a significant increase in TMB absorption is observed when the CoCuMo‐LDH nanosheets were incubated at pH 5.4 containing GSH. In contrast, the CoCuMo‐LDH nanosheets incubated at pH 7.4 and 6.5 with GSH show inconspicuous increase in TMB absorption, illustrating the pH‐responsive ·OH generation capacity of the CoCuMo‐LDH nanosheets.…”
Section: Resultsmentioning
confidence: 98%
“…For example, inorganic-based NPs are potentially toxic due to their relatively high stability, which may cause greater uncertainty in vivo . 113,114 To solve these problems, there are two main approaches, one is to increase the biodegradability of inorganic NPs, and the other is to improve their renal clearance efficiency. 115 Notably, the performance of inorganic NPs are closely related to their size, implying that their properties may change dramatically due to degradation and causing damage to tissues and organs during metabolism.…”
Section: Classifications Of Nps For Intracellular Cargo Deliverymentioning
confidence: 99%
“…Na 2 S was used to mimic endogenous H 2 S, and TEM images showed that Co‐POM assembled into POM‐CoS nanoclusters upon reaction with Na 2 S, and the solution also changed from colorless to black, and its hydrated particle size also changed significantly(Figure 6c). [33] Thus, in combination with the depletion of the overexpressed reduced substance H 2 S to increase ROS, Co‐POM itself assembled into POM‐CoS nanoclusters with photothermal properties. The biodegradation of POM‐CoS releases Co 2+ through the Fenton‐like reaction to produce ⋅OH and the Russell mechanism to produce 1 O 2 , enabling a synergistic photothermal and chemodynamic treatment of colon cancer.…”
Section: The Biological Process Of Ros Therapy Induced By Pommentioning
confidence: 99%